2022
DOI: 10.3390/ani12243456
|View full text |Cite
|
Sign up to set email alerts
|

Surfactin Containing Bacillus licheniformis-Fermented Products Alleviate Dextran Sulfate Sodium-Induced Colitis by Inhibiting Colonic Inflammation and the NLRP3 Inflammasome in Mice

Abstract: Inflammatory bowel disease (IBD) is a non-infectious disease characterized by chronic inflammation of the gastrointestinal tract. Currently, management of IBD is still a clinical challenge. The purpose of this study was to investigate the therapeutic potential of surfactin containing Bacillus licheniformis-fermented products (SBLF) and commercial surfactin (CS) on the treatment of dextran sulfate sodium (DSS)-induced colitis in a mouse model. We found that mice that received drinking water containing 3% DSS de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…In particular, the spleen index is closely related to adaptive immune responses as the spleen serves as a site for immune cell proliferation and differentiation [ 27 ]. Previous studies have shown that the spleen enlarges under immune activation during the occurrence and development of colitis [ 28 , 29 ]. We observed that DSS induction significantly increased the spleen index in mice, while treatment with S. boulardii , heat-killed S. boulardii , and S. boulardii β-glucan reduced the spleen index, indicating an immunomodulatory effect on UC mice.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the spleen index is closely related to adaptive immune responses as the spleen serves as a site for immune cell proliferation and differentiation [ 27 ]. Previous studies have shown that the spleen enlarges under immune activation during the occurrence and development of colitis [ 28 , 29 ]. We observed that DSS induction significantly increased the spleen index in mice, while treatment with S. boulardii , heat-killed S. boulardii , and S. boulardii β-glucan reduced the spleen index, indicating an immunomodulatory effect on UC mice.…”
Section: Discussionmentioning
confidence: 99%
“…Te YerP protein has been implicated in the surfactin export [43]. B. subtilis, B. licheniformis, B. amyloliquefaciens, and B. sonorensis produce an important type of biosurfactant that includes lipoproteins and lipopeptides such as surfactin [44][45][46][47]. We also postulate that Rose Bengal treatment indirectly afects the surfactin export by afecting the function of YerP or related export proteins, such as YcxA and KrsE [43], which then prevent the YerP-surfactin interaction.…”
Section: Discussionmentioning
confidence: 99%
“…It promotes an increased percentage of T cells in the mesenteric lymph nodes and spleen and higher levels of sIgA and IgG in the gut . Administrating B. licheniformis to mice with water improves their condition by reducing inflammation of the colon mucosa and inhibiting the activation of inflammatory processes (Tsai et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%